Review on Effects of NSAID`S on Different Systems - Puppala, Naresh; Reddy, Gantala Alekhya (Asian Journal of Pharmaceutical Research and Development, 2020)
Non steroidal anti-inflammatory drugs (NSAIDs) are amongst the most commonly prescribed medication. Some are available over the counter and likely to be abused. The gastrointestinal (GI), renal and cardiovascular (CV) side effects limit NSAIDs use. These side effects occurred at a rate as low as 1%–5% for NSAID users. The gastrointestinal (GI), renal and cardiovascular (CV) side effects limit NSAIDs use. Some studies have shown that an extra 2to8 per 1000 people per year may have a major vascular event from using an NSAID. Several studies demonstrated that conventional NSAIDs were associated with a higher risk of AKI and GN and decreased kidney hemodynamic functions, including sodium excretion. NSAIDs have a range of adverse effects mainly affecting the GI, renal and CV systems.